Indigenous Research Methodologies in Sámi and Global Contexts - Kristiina Virtanen, Pirjo; Keskitalo, Pigga; Olsen, Torjer (New Research - New Voices, 2021)
This book addresses the conceptualization and practice of Indigenous research methodologies especially in Sámi and North European academic contexts. It examines the meaning of Sámi research and research methodologies, practical levels of doing Indigenous research today in different contexts, as well as global debates in Indigenous research. The contributors present place-specific and relational Sámi research approaches as well as reciprocal methodological choices in Indigenous research in North-South relationships. This edited volume is a result of a research collaboration in four countries where Sámi people live. By taking the readers to diverse local discussions, the collection emphasizes communal responsibility and care as a key in doing Indigenous research. Readership: All those interested in research methodologies, Indigenous studies and Sámi research in particular, as well as all those interested in research concerned with Indigenous societies and how to implement decolonial approaches into research.